Pelatihan dan Pendampingan Teknologi Informasi Pengembangan Gampong Digital Gampong Uteunkot Berbasis Web di Kota Lhokseumawe - Ilhadi, Veri; Aidilof, Hafizh Al Kautsar; Fakhrurrazi; Sahputra, Ilham; Zohra, Siti Fatimah A; Angelina, Difa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This program aims to enhance information technology capabilities in Uteunkot Village, Lhokseumawe City, focusing on developing web-based digital villages. The initiative includes training and assistance for village residents to support the village apparatus in public services, archiving, and marketing for MSMEs. The training aims to facilitate archiving at the Geuchik office through digital public service and archiving socialization, accompanied by website development training for the village. The web application is designed to present relevant and beneficial information for village residents with an efficient interface. The results of the digital web training and assistance indicate that villages in Indonesia are now more connected and can access broader information, contributing to increased community knowledge. The digitalization of public services has accelerated administrative processes, enhanced transparency, and facilitated interactions between village governments and their residents. Additionally, the training enhances the digital skills of village officials, increasing their capacity to utilize web-based technology. The implications of this training suggest that villages can transform to be smarter and more competitive in the digital era